Near constant groundwater recharge efficiency under global change in a central European catchment. Issue 2 (31st January 2023) - Riedel, Thomas; Weber, Tobias K. D.; Bergmann, Axel
Abstract: The fraction of precipitation that infiltrates soils and subsequently becomes recharge is one of the principle components of an unconfined aquifer's water budget (this fraction is here termed recharge efficiency). Here we tested how recharge efficiency will respond to climate change including a possible plant physiological response to climate change (e.g., stomatal closure; increasing leaf area) in a catchment used for drinking water production in western Germany. To this end we used a soil water model (HYDRUS‐1D) forced with climate data spanning the time period from 1971 to 2099. Three different vegetation types were considered: turf grass representing the primary infiltration sites within residential areas; maize representing the main crop on agriculturally used land; and beech representing the forested parts of the catchment. We found that, the positive effects of climate change on recharge efficiency (more rain during the main recharge season in winter, less crop water demand due to faster plant ripening in spring and summer, increased plant water use efficiency, reduced global radiation as cloud density increases) were not completely compensated by the negative effects (less precipitation, higher leaf area index and increasing vapour pressure deficit in summer season) at our study site. Because total annual precipitation increased slightly until the end of the 21th century, changes in the amount of total annual recharge were also positive, though moderate (up to +20% change in the period 2071–2099 as compared to 1970–2000). The results of this study will be helpful for water authorities managing water rights under the perspective of a changing climate. In the future, our study site is expected to receive sufficient recharge from precipitation to maintain current rates of groundwater withdrawal for public water supply and irrigation. Thus, the region's agriculture sector may become a 'global warming winner, ' when cropping in other regions in Europe may increasingly suffer from drying conditions during the growing season. Abstract : A soil water balance simulation shows that recharge efficiency (the fraction of precipitation that infiltrates into a soil to eventually become recharge) remains almost constant during the 21th century in Western Germany. Including a physiological response of plants to climate change does not severely alter the simulated soil water fluxes.